An exercise of functional analysis: the psychologist performance in menopause groups (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
This article is an exercise which functionally analyzes the verbal behavior of members of a menopause group (including the psychologist's). The three-term contingency model (antecedent-behavior-consequence) was applied. Three preliminary steps were taken: an explanation of what functional analysis consists of, an explanation of the functioning of menopause groups and the preparation for the group functional analysis (choice of the verbal behavior as target behavior for analysis, count of the frequency of the members' speech, selection of the psychologist's speech as the target behavior and its categorization). In the last part of the article the category of giving information, the most frequent category of the psychologist's verbal behavior was analyzed as a function of its antecedents and consequences and then inserted in the three-term contingency model.